High dose rate brachytherapy boost for prostate cancer: Biochemical control and the impact of transurethral resection of the prostate and hydrogel spacer insertion on toxicity outcomes. Issue 3 (25th March 2019) - Chao, Michael; Bolton, Damien; Lim Joon, Daryl; Chan, Yee; Lawrentschuk, Nathan; Ho, Huong; Spencer, Sandra; Wasiak, Jason; Guerrieri, Mario; Ow, Darren; Troy, Andrew; Pham, Trung; et al.
Abstract: Introduction: To examine the long‐term outcomes of high dose rate brachytherapy boost (HDR‐BT) combined with external beam radiotherapy (EBRT) for intermediate and high‐risk prostate cancer patients. Methods: Data from 95 patients who underwent combined EBRT (50.4 Gy) and HDR‐BT to the prostate between 2010 and 2017 were retrospectively analysed. Biochemical progression free survival (bPFS), local recurrence free survival (LRFS), metastatic free survival (MFS) and overall survival (OS) were estimated using Kaplan–Meier method. Regression analysis was conducted to identify important predictors of outcomes. Results: A total of 24 patients received an initial HDR‐BT dose of 18 Gy in three fractions, with the remaining 71 patients receiving 16 Gy in two fractions as per departmental protocol changes. Most patients (88%) received androgen deprivation therapy. A transurethral resection of the prostate (TURP) was performed in 14 patients and hydrogel spacers (HS) were used in 30 patients. Median follow‐up was 58 months. The 5‐year bPFS, LRFS, MFS and OS were 92%, 100%, 92% and 88%. Univariate regression revealed no statistical association between patient characteristics and time to relapse (all P > 0.1). Late > grade 2 genitourinary (GU) toxicity was 6.3%. The use of HS or prior TURP had no impact on late GU toxicity. Late Grade 1 gastrointestinal (GI) toxicity was 5.3%. Conclusion: The combined HDR‐BT with EBRT resulted in excellent bPFS. The cumulative risk of late GU and GI toxicity was low and can be further improved with preventative strategies such as a pre‐emptive TURP and/or HS insertion.